Second-generation antipsychotics and the risk of chronic kidney disease: a population-based case-control study. Issue 8 (11th August 2020) - Højlund, Mikkel; Lund, Lars Christian; Herping, Jonas Leander Emming; Haastrup, Maija Bruun; Damkier, Per; Henriksen, Daniel Pilsgaard
Abstract : Objectives: To examine the association between use of second-generation antipsychotics (SGA) and the risk of chronic kidney disease (CKD). Design: Population-based case-control study. Setting: Routinely collected laboratory, prescription and diagnostic information on all inhabitants with creatinine measurements residing on the island of Funen, Denmark (2001 to 2015). Participants: 21 434 cases with incident CKD matched with 85 576 CKD-free population controls by risk-set sampling using age, sex and calendar year. Primary and secondary outcome measures: CKD was defined as an estimated glomerular filtration rate below 60 mL/min/1.73 m 2 in a period longer than 3 months. Information on drug exposure and comorbidities were obtained from the Danish National Prescription Register and the Danish National Patient Register. We calculated OR for the association between SGA use and CKD using conditional logistic regression. Results: Use of SGAs was associated with increased risk of CKD among ever users (OR 1.24, 95% CI: 1.12 to 1.37) and current users (OR 1.26, 95% CI: 1.12 to 1.42). We found no clear evidence of dose-response relationship. Both short duration (one to two antipsychotic prescriptions; OR 1.22, 95% CI: 1.01 to 1.48) as well as long-term use (>30 prescriptions; OR 1.45, 95% CI 1.19 to 1.76) were associated with an increased risk of CKD. Both use of SGAs with mild and high risk of metabolic disturbances was associated with increased risk of CKD (OR 1.21, 95% CI: 1.06 to 1.39 and OR 1.36, 95% CI: 1.11 to 1.68, respectively). Recent use of non-steroidal anti-inflammatory drugs, prior use of lithium, hypertension or prior acute kidney injury were not clearly associated with development of CKD connected to SGA exposure. The highest risk of CKD was found for clozapine (OR 1.81, 95% CI: 1.22 to 2.69). Conclusion: Use of SGA is associated with a small-to-moderately increased risk of incident CKD. All investigated SGAs, except for aripiprazole, were associated with an increased risk of CKD.